Coagulation Studies in 45 Cases of Nephrotic Syndrome without Uremia - Kanfer, A; Kleinknecht, D; Broyer, M; Josso, F (Thrombosis and Haemostasis, 1970)
Coagulation studies were performed in 45 cases of nephrotic syndrome without uremia. The most striking features were an increase in the number of thrombocytes, and in the level of fibrinogen, factor V and factor VIII. Thrombin time was usually prolonged and the titre of antithrombin III was increased. No fibrin breakdown products were found in the serum. 13 patients developed thrombotic complications, with eventual death in 5 cases.